Analisis Rasio Likuiditas Terhadap Kinerja Keuangan PT Garuda Indonesia Pada Masa Pandemi (2020) - Gea Mustika; Intan Nur Apriliani (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
PT Garuda Indonesia is one of the first Indonesian airlines that is leading in the world of air transportation services. During the pandemic, especially 2020, the company was threatened with bankruptcy. This study focuses on the analysis of the liquidity ratio on the financial performance of PT Garuda Indonesia during the pandemic in 2020. The purpose of this study is to determine the financial performance of PT Garuda Indonesia in terms of its liquidity ratio and to determine the company's strategy in overcoming financial problems. The research method and the type of data used by the author in this study is a quantitative method, namely by analyzing and describing financial statement data obtained numerically as in the financial statements of PT Garuda Indonesia. The results of this study can be seen that in the 2020 period PT Garuda Indonesia experienced several obstacles and decreases according to the calculation of the liquidity ratio in terms of the current ratio, quick ratio, and cash ratio compared to previous years. This was due to a decrease in the number of flights during the pandemic which had an impact on airline operations and liquidity.